CODE-SWITCHING IN ENGLISH TEACHING PROCESS: A STUDY OF LECTURERS’ UTTERANCE AT DEPARTMENT OF ENGLISH EDUCATION - Faurina Anastasia (Institut Agama Islam Negeri (IAIN) Bone, 2022)
Code-mixing or code-switching in English teaching and learning used in EFL classroom, especially to enhance understanding skill in English. Code-mixing and code-switching in teaching process will make language learning more meaningful and effective (Liu, 2008). Most studies of code-mixing and code-switching easily found in oral communication, such as in daily communication or formal situation. A lot of research on code-mixing and code-switching were not mention the specific process of those codes in learning process (Kim, 2006; Marzona, 2009; Saputro, 2013; Siregar and Sumarsih, 2014; Ansar, 2017; Oladosu, 2011; Mustain, 2011; Siskawati, 2021). The other gaps are most of the research sites were in junior high school and senior high school and others from television, newspaper, magazine, television program, etc. Then other different is they used teacher, students and group of society as the sample of research. In this research, lecturer of Department of English Education became sample of the research and university as site of the research. Objective of the research is to find out kind of code-switching uttered by the lecturer in teaching process at Department of English Education and the factors influencing code-switching. Method used in this research is descriptive qualitative. The subjects of the research are two lecturers of Department of English Education. The instrument consists of documentation of descriptive observation (by joining class group platform) and list of interviews on August 2021. In analyzing the data, the researcher observed the learning process through online platform, recorded the lecturer utterance, transcribed the recording, classified the data into kinds of code-switching used by the lecturer based on Romaine’s theory (1995), then calculated the percentage of each kind of code-switching. The researcher analyzed the factor why the lecturer used code-switching in teaching process based on the recording of interview and draw a conclusion by using Holme’s theory (1992). The result showed there are two types of code-switching used by the lecturer, namely inter-sentential switching (57,5%), intrasentential switching (42,5%), and there was not tag-switching. The data of interview showed the reason of lecturer used code-switching in teaching process because of the participant, setting or social context, topic, and function.